2015
DOI: 10.1016/j.bbadis.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Leptin modulates human Sertoli cells acetate production and glycolytic profile: a novel mechanism of obesity-induced male infertility?

Abstract: Human feeding behavior and lifestyle are gradually being altered, favoring the development of metabolic diseases, particularly type 2 diabetes and obesity. Leptin is produced by the adipose tissue acting as a satiety signal. Its levels have been positively correlated with fat mass and hyperleptinemia has been proposed to negatively affect male reproductive function. Nevertheless, the molecular mechanisms by which this hormone affects male fertility remain unknown. Herein, we hypothesize that leptin acts on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 69 publications
2
79
0
Order By: Relevance
“…Studies showed that leptin can directly interact with its receptors on Leydig cells and regulates the synthesis of steroids within the testicles. 91,92 Leptin can modulate the firing rate of gonadotropins as well. 27 High amounts of leptin have been associated with impaired spermatogenesis and infertility, probably as a result of insufficient gonadotropin support, which leads to lower sperm quality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that leptin can directly interact with its receptors on Leydig cells and regulates the synthesis of steroids within the testicles. 91,92 Leptin can modulate the firing rate of gonadotropins as well. 27 High amounts of leptin have been associated with impaired spermatogenesis and infertility, probably as a result of insufficient gonadotropin support, which leads to lower sperm quality.…”
Section: Discussionmentioning
confidence: 99%
“…At concentrations found in healthy lean men, leptin is able to upregulate the protein levels of GLUT2, whereas concentrations of leptin found in lean and obese patients increases the activity of LDH, the enzyme that catalyses the production of lactate necessary for the developing germ cells. Notably, all the concentrations of leptin decrease acetate production by Sertoli cells (Martins et al 2015), which could be associated with alteration in the cells lipid droplet accumulation. Accumulation of cytoplasmic lipid droplets, which has been associated with the elimination of germ cell-derived apoptotic bodies by phagocytosis (Wang et al 2006), was reported as one of the most striking deleterious effects of hyperthermia in Sertoli cells (Valles et al 2014).…”
Section: Energy Balance Hormonal Dysfunction and Male Reproductionmentioning
confidence: 94%
“…Therefore, a higher adipose tissue mass means higher leptin blood concentration, and obesity is associated to the highest values. GLUT expression is upregulated by leanlike leptin concentrations in Sertoli cells, but not by obese-like concentrations, although in both conditions acetate production was inhibited and LDH activity increased [21]. This data suggests a metabolic reroute towards β-oxidation using fatty acids as preferred substrate.…”
Section: Open Access Http://scidocorg/ijdvrphpmentioning
confidence: 80%